A influência do território sobre as escolhas escolares das famílias: um estudo em uma região da periferia de Belo Horizonte - Gustavo Bruno de Paula (2015)
The research question of this dissertation is in the confluence of classical problems of sociology of education and urban sociology. Aiming to understand if and how socio-spatial inequalities influence or reinforce schooling inequalities, we analyzed the way certain social and urban characteristics of a territory configure the strategies and families school choices. In order to do so, we delimitated as a geographical observation space two sub-regions in the Barreiro area, in the city of Belo Horizonte, that present socioeconomic and urban contrasts. We compared the strategies used and school choices made by families that lived in these two areas, aiming to identify how the socio-economic characteristics of the environment restrained or favored their schooling aspirations. The territorial factors considered were: social and urban conditions of the territory, especially those related to schooling; the symbolic divisions of the physical space, such as the stigma or prestige of the neighborhoods; and the process of collective socialization, for instance the relation established by families with their vicinity. To describe and analyze the territory, we did a research on secondary data in several sources, such as IBGE, INEP, and Fundação João Pinheiro/FJP, as well as documental research in official documents on the history of the region. Primary empirical data was collected through interviews with 17 mothers and/or fathers, using a semi-structured list of questions that approached issues related to the families life conditions; their relation with the territory; and their strategies and school choices. In order to complement the data on schooling offer in the area, we interviewed four education professionals (two principals, one vice-principal, and an educational supervisor) of different schools in the two sub-regions. The results indicate that the main impact of the territory comes from the quantitative and qualitative characteristics of school offer (number and quality/reputation of the existing schools), although it has been observed that the social differences of the territory also influences parental choices, mainly families that lived in underprivileged areas. The importance of aspects connected to collective socialization and social contacts were reduced, as they depend on families social positions.